PENGARUH PENDAPATAN PAJAK DAERAH, RETRIBUSI DAERAH DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Achmad Zuhdi (2017)
This study aims to see whether there are influence of Development tax, Regional Retribution and Balance Fund on Local Government Financial Performance. The study uses of 68 province in indonesian in 2014, 2015. Sampling technique using purposive sampling (purposive sampling method). Testing the hypothesis is used multiple linear regression analysis with SPSS 23 and a significance level of 5% (0,05). The results of the testing showed that : (1) there is no significance influence of Development Tax on Local Government Financial Performance, (2) there is significance influence negative of Regional Retribution on Local Government Financial Performance,(3) there is significance influence negative of Balance Fund on Local Government Financial Performance.